The SAGE handbook of social gerontology - Dannefer, Dale.; Phillipson, Chris; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2010)
This volume reflects the emergence of ageing as a global concern, including chapters by international scholars from Asia Australasia, Europe and North America. It provides a comprehensive overview of key trends and issues in the field drawing upon the full range of social science disciplines.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social gerontology; Aging -- Social aspects; Older people -- Social conditions; Social networks; Electronic books